Traitors, cowards, martyrs, heroes - Remec, Meta (Studia Historica Slovenica, 2023)
The article deals with the phenomenon of youth suicide and attitudes towards suicide in Slovenia after World War II. Based on the police and State Security Service (SDV) reports on suicides, memoirs, newspaper articles, and other materials collected by investigators (such as suicide notes and witness statements), the article sheds light on the social conditions in Slovenia during the 1960s, analyses the discourse of the authorities, the media, and experts in psychiatry, psychology, and criminology on the subject of youth suicide, and highlights the methods used by the socialist authorities to control the citizens. The second part of the article focuses on the police investigation of nine suicides and five attempted suicides of public figures' children, which the authorities considered particularly problematic because the deceased youth were socially engaged, educated, and privileged individuals whose deaths attracted public attention.
Keywords: 1968; Aleš Kermauner; Borivoj Dedijer; Borut Kardelj; Jugoslavija; mladina; samomor; Slovenija; socialism; socializem; suicide; Svit Brejc; youth; Yugoslavia